Acupuncture's Emergence as A Promising Non-Pharmacological Therapy for Appetite Management in Cancer Chemotherapy. - Zhang, Xu; Yang, Wenjing; Shang, Junliang; Shi, Lin; Yang, Lu; Zhang, Chi; Chen, Yuyi; Liu, Zishen; Li, Bo; Zhang, Xinghan; Tong, Li; Yang, Guowang (Nutrition & Cancer, 2025)
Objective: The primary objective of this investigation was to assess the impact of acupuncture intervention and explore the intricacies of acupoint selection as a therapeutic strategy for chemotherapy-induced Anorexia (CIA). Method: Eight electronic databases were searched to identify relevant studies on the use of acupuncture for the treatment of CIA to conduct a comprehensive meta-analysis. Following this, the Apriori algorithm, correlation analysis, and cluster analysis were performed to identify correlations between the selection of acupoints. Results: Acupuncture significantly reduced the incidence of anorexia (RR = 0.76, 95%CI: 0.65, 0.90; I2=63%; p = 0.001; n = 503) and anorexia score (SMD=-0.33, 95%CI: −0.53, −0.14; I2=22%; p = 0.0008; n = 419), as well as preserved body mass (MD = 2.70, 95%CI: 1.08, 4.32; I2=0%; p = 0.001; n = 187) and enhanced physical strength (MD = 4.23, 95%CI: 1.90, 6.55; I2=58%; p = 0.0004; n = 377). Moreover, subgroup analysis highlighted its efficacy in managing anorexia associated with non-gastrointestinal tumors and mitigating the severity of cisplatin-induced anorexia. Meanwhile, Zusanli (ST36), Neiguan (PC6), Tianshu (ST25), Zhongwan (RN12), and Qihai (RN6) were identified as crucial acupoints in CIA management. Conclusion: Acupuncture holds promise as a potential non-pharmacological approach for managing anorexia during cancer chemotherapy. To provide robust evidence of its effectiveness, well-designed Randomized Controlled Trials (RCTs) with larger participant cohorts, and consistent core outcome measures are essential.